Engineering Tissue‐Specific, Multiscale Microvasculature with a Capillary Network for Prevascularized Tissue (Small Methods 10/2021). Issue 10 (28th October 2021) - Son, Jeonghyun; Hong, Sung Joon; Lim, Jun Woo; Jeong, Wonwoo; Jeong, Jae Hyun; Kang, Hyun‐Wook
Abstract : Back Cover In article number 2100632, Kang and co‐workers provide a novel printing technology for the fabrication of multiscale microvasculature to mimic the hierarchical architecture of the human microvascular system. The millimeter‐scale vessels were produced with direct printing of sacrificial bio‐ink and capillary‐scale vessels were generated within the user‐designed bridge pattern and induced by the angiogenic factors from the fibroblast pattern.